2012
DOI: 10.4102/sajesbm.v5i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Guidance for SMEs with the adoption of technology: A conceptual framework

Abstract: When starting up a new small or medium sized company, it is crucial to understand what the requirements are in terms of Information and communication technologies (ICT). Bentellis and Boufaïsa (2008) note that over the last twenty years the markets have been changing fast, which has led to the evolution of the business environment. In many instances companies cannot keep up with the change occurring in the ICT arena. Entering the market as a small competitor, you need to ensure that you implement ICT that will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…We also noted a relationship between ICT compatibility and age of the firm, shown by a Kruskal–Wallis coefficient of p ≤0.02 (see Appendices A and B). Consistent with these results, Steyn and Leonard () also found ICT compatibility with a user's job functions to be an important factor in the adoption and use of ICT. Looking at the relationship between the educational levels of the owner‐managers and ICT compatibility in the firms, 22 of the owner‐managers with a tertiary qualification (17% of respondents) and 21 having a degree or above (16% of respondents) reported that adopted ICT was compatible with existing organizational systems.…”
Section: Resultsmentioning
confidence: 63%
“…We also noted a relationship between ICT compatibility and age of the firm, shown by a Kruskal–Wallis coefficient of p ≤0.02 (see Appendices A and B). Consistent with these results, Steyn and Leonard () also found ICT compatibility with a user's job functions to be an important factor in the adoption and use of ICT. Looking at the relationship between the educational levels of the owner‐managers and ICT compatibility in the firms, 22 of the owner‐managers with a tertiary qualification (17% of respondents) and 21 having a degree or above (16% of respondents) reported that adopted ICT was compatible with existing organizational systems.…”
Section: Resultsmentioning
confidence: 63%
“…This sector tends to differ from large enterprises in that they stimulate competition, bring about a diversity of products and services, have increased flexibility in their internal and external systems and possess hands-on managerial style, which facilitates faster decision-making (Kendall et al, 2001). Adoption of e-marketing strategies can go a long way in representing the small business sector in the national economy in order stay ahead and maintain a competitive advantage (Steyn & Leonard, 2012). However, in South Africa alone, SMEs contribute 37 percent to employment (Soontiens, 2002;Barry & Milner, 2002).…”
Section: The Sme Sector and Its Importancementioning
confidence: 99%
“…SMMEs usually act on gut feeling and are easily influenced by current trends in the environment without paying attention to the functionality and appropriateness of the technology to their business. Steyn and Leonard (2012) reveal that many SMME owners often seek the assistance of friends, relatives or other SMME owners in the initial process of adopting new technology. Giving the lack of adequate ICT knowledge and limited exposure to new technology from the people consulted for advice, SMMEs do not necessarily adopt suitable technology because of their ignorance of the potential value and use of technology (Abulrub et al 2012;Palvalin et al 2013).…”
Section: Findings and Discussionmentioning
confidence: 99%